Beyond the Black Box: Towards a Theology of the Artifact and the Phronetic Validation of AI-Mediated Liturgy in Madagascar - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2027)
This study investigates the ontological and methodological transition from Paul Tillich’s classical correlation to a paradigm of Augmented Correlation within the liturgical context of the Fiangonan’i Jesoa Kristy eto Madagasikara (FJKM). Facing the dual pressures of temporal scarcity and the need for theological depth, this research proposes the